WAMS Cyber-Physical Test Bed for Power System, Cybersecurity Study, and Data Mining - Adhikari, Uttam; Morris, Thomas; Shengyi Pan (IEEE transactions on smart grid, 2017)
Researchers from various cross disciplinary fields such as power systems, data science, and cybersecurity face two distinct challenges. First, the lack of a comprehensive test bed that integrates industry standard hardware, software, and wide area measurement system (WAMS) components and protocols impedes the study of cybersecurity issues including vulnerabilities associated with WAMS components and the consequences of exploitation of vulnerabilities. Second, a lack of comprehensive labeled Synchrophasor data along with other system related information imposes challenges to the development and evaluation of data mining algorithms that can classify power system cyber-power events. In this paper, a WAMS cyber-physical test bed was developed using a real time digital simulator with hardware-in-the-loop simulation. Commercial control and monitoring devices, hardware, software, and industry standard communication networks and protocols were combined with custom MATLAB, Python, and AutoIt scripts to model realistic power system contingencies and cyber-attacks. An automated simulation and control engine was developed to randomize modeled cyber-power events including power system faults, contingencies, control actions, and cyber-attacks. Scripts were added to capture heterogenous sensor data and create ground truth labeled datasets. The WAMS cyber-physical test bed is capable of simulating various sized power systems and creating datasets without altering the hardware configuration. A WAMS architecture is presented to document the integration of various components. Finally, test bed applications, simulated cyber-power scenarios, the dataset development process, and selected results are presented.